Hypothyroidism, Motor Clumsiness, and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The behavioral characteristics of 63 children with early-treated congenital hypothyroidism (CH) were evaluated by parent and teacher ratings and compared to 34 healthy controls (ages 7.5-9.5 yrs) at the University of Jyvaskyla, Finland.